Literasi dan Harmonisasi Sosial: Desain Literasi Digital Berbasis Kearifan Lokal pada Masyarakat Pedesaan - Ari Wibowo; Basri Basri (IAIN Palangka Raya, 2020)
This study aims to develop a digital literacy design based on local wisdom so that it can support social harmony in rural communities in Bangka Regency. The development of this literacy design is motivated by the high accessibility of rural communities to the use of the internet and social media, but it is not accompanied by good digital literacy skills. This study uses the Research and Development (R&D) method by adapting the Thiagarajan development cycle model which consists of four 4-D stages (define, design, develop, and disseminate). At the define stage, observations and interviews were carried out on several informants, the result was that five findings were analyzed and identified for the next stage. In the design stage, eight digital literacy components were obtained which were adapted from the Digital Literacy Across the Curriculum and adapted the Wilbur Schramm matrix format for media development, the result was that there were nine media formats that were relevant to use for local wisdom- based digital literacy. At the development stage, a small-scale test was carried out on 15 respondents, the percentage of the practicality of the media was on average 85.5%, meaning that the media was very practical to use, while in the large-scale test on 30 respondents, an average of 93.7% was obtained, the percentage of practicality the highest is in the aspects of interest and material literacy. Specifically for the development of the material aspects, there are 6 themes that are prioritized to support social harmonization in rural communities in Bangka Regency, including; 1) religious moderation, 2) tolerance, 3) prevention of hoaxes (fake news); 4) hate speech; 5) racial issues, and 6) prevention of the doctrine of religious radicalism.Keywords : Digital Literacy, Social Harmony, Local Wisdom, Rural Community